2022
DOI: 10.15567/mljekarstvo.2022.0402
|View full text |Cite
|
Sign up to set email alerts
|

Novel probiotic camel milk yoghurt supplemented with inulin: antibacterial, antioxidant and antidiabetic effects

Abstract: Similar to cow’s milk, camel milk also contains the essential nutrients as well as potentially therapeutic compounds with antihypertensive, and antioxidant properties. In the current study, camel milk was used for developing a new probiotic camel milk yoghurt with commercial prebiotic (inulin). The camel yoghurt samples were evaluated by monitoring the changes in some physicochemical properties (pH, total acidity and synerisis) and bacterial viability and survival of Limosilactobacillus fermentum CABA16 during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Milk is composed of essential nutrients for the growth of microorganisms and several studies have revealed microbiological contamination and abundance and/or unsafe quality level at a high prevalence with the major culprits including Listeria monocytogenes 1 , 2 . Milk, a primary animal-based protein source in consumer’s diet occurs in varieties such as raw, fermented, powdered, and/or pasteurized milks 3 , 4 with different degree of microbial exposure and contaminations. Following the dietary relevance of milk, composition and its associated preservation strategy, milk has become the major module for bacterial proliferation and contamination 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Milk is composed of essential nutrients for the growth of microorganisms and several studies have revealed microbiological contamination and abundance and/or unsafe quality level at a high prevalence with the major culprits including Listeria monocytogenes 1 , 2 . Milk, a primary animal-based protein source in consumer’s diet occurs in varieties such as raw, fermented, powdered, and/or pasteurized milks 3 , 4 with different degree of microbial exposure and contaminations. Following the dietary relevance of milk, composition and its associated preservation strategy, milk has become the major module for bacterial proliferation and contamination 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cow's milk, camel's milk contains important nutrients as well as potentially therapeutic compounds with antihypertensive and antioxidant properties (Mahmoudi et al, 2022). Mastitis is one of the most problematic diseases in dairy animals around the world, caused by a wide range of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat contains a large number of fatty acids, some of which are of great interest (Mahmoudi et al, 2022). Saturated fatty acids, especially C12:0, C14:0 and C16:0, are commonly attributed negative effects on human health, while other fatty acids such as linoleic and α-linolenic acids and oleic acid (c9-C18:1) are said to have beneficial effects and to prevent the onset and development of some chronic diseases.…”
Section: Introductionmentioning
confidence: 99%